REPLENISHMENT OF FUNDS OF PERSONAL ORIGIN IN THE ARCHIVES OF KAZAKHSTAN: METHODOLOGICAL AND LEGAL FOUNDATIONS, CURRENT STATE AND PROBLEMS (Journal of history-rus, 2022)
The collection of documents collected during the life and work of outstanding historical figures of the country, public figures, representatives of culture and art, scientists, heroes who have made a lot of efforts to renew and revive culture, language, Kazakh traditions and customs, is called the documents of the foundation of personal origin. The broad development of the Kazakh people, having joined the international community during its current independence, has brought intellectuals of the Kazakh nation all over the world into the world of socio-political relations at the international level. Archival documents about their services to the people, their contribution to the prosperity of the state are a precious treasure, an inexhaustible wealth for our national ideology. One of the most important tasks is to analyze and pass on its value to the next generations. The article defines the issues arising in the work on the replenishment of documents of personal origin in the republican archives of Kazakhstan (Central State Archive, Presidential Archive, Central State Archive of Scientific and Technical Documentation). The methodological, regulatory and legal basis of replenishment work is analyzed. Contracts concluded between archives and well-known persons are analyzed and compared. Recommendations are given on improving methodological recommendations, work on completing documents of personal origin. Key words: archive, funds of personal origin, replenishment, methodological manual, regulatory framework.